THE EFFECT OF TRAFFIC FACTORS AND TECHNOLOGY FACTORS ON CHRONOLOGICAL DELAY OF EMERGENCY (115) ON THE BESIDES OF INJURED PEOPLE IN BOYER AHMAD CITY IN 2017 - Sadat, Seyed Ehsan; Barzabad, Parviz Aghayii; Asl, Iravan Masoudi (Universal Journal of Pharmaceutical Research, 2018)
Objective: The aim of this study is to investigate traffic factors and technology factors on chronological delay of emergency (115) on the besides of injured people in Boyer Ahmad city in 2017. The research method of this investigation from the point of view related to target is operational and according to nature is descriptive-analytic. Methods: The target population is users of 115 emergency services of Boyer Ahmad city from the first of March to August 2017. On the basis of the similar statistics of the first six months of 2016, 2240 people have used emergency services of Boyer Ahmad city that on the basis of Krejcie and Morgan table, 100 people will be chosen as statistical sample. In this study, data has been gathered by using researcher made questionnaire. At first, needed data has been achieved by responses to questionnaires and then study variables have been tested and analyzed by using SPSS statistical software and statistical methods in two sections of descriptive and perceptive. Results: The results of the study indicated that there is a meaningful relation between environmental, relational and traffic factors and also between technological factors and 115 emergency delay on the patient’s beside in Boyer Ahmad city (p>0.05). Conclusion: In conclusion as, the meaningfulness level and correlation coefficient between studied variables with 115 emergency delay respectively are: traffic factors (P=0.001, r=0.73), technology factors (P=0.001, r=0.62). So, research hypothesis is verified. Peer Review History: Received 26 July 2018; Revised 8 September; Accepted 24 October, Available online 15 November 2018 Academic Editor: Dr. Iman Muhammad Higazy , National Research Center, Egypt, imane.higazy@hotmail.com Reviewer(s) detail: Dr. Masoumeh Divar , Shiraz University, Shiraz, Iran, zhaledivar@gmail.com Mohaddese Mahboubi , Alzahra University, Tehran, Iran, mahboubi@barijessence.com